Gap analysis of land availability and land needs to identify potential development of agricultural lands in Santan watersheds, East Kalimantan, Indonesia - AKHMAD SOPIAN; SIGIT HARDWINARTO; MARLON IVANHOE AIPASSA (Society for Indonesian Biodiversity, 2019)
Abstract. Sopian A, Hardwinarto S, Aipassa MI, Sumaryono. 2019. Gap analysis of land availability and land needs to identify potential development of agricultural lands in Santan watersheds, East Kalimantan, Indonesia. Biodiversitas 20: 1097-1105. Pressures caused by high population growth in various places increase the needs for lands. The aims of this research are to determine the availability and needs of agricultural lands in Santan 1 and Santan 2 watersheds, East Kalimantan, Indonesia as well as to classify land capability which are key aspects in managing land resources. Land availability was determined based on the local actual total production of all commodities, such as agriculture, plantation, and livestock at the sub-district level. Land needs were determined based on the land area required for decent life needs per resident. While land capability was determined using weighting analysis of the limiting factors. Results of this study show that land availability on Santan 1 and Santan 2 watersheds is inadequate to fulfill the needs of inhabitants for agricultural lands. There are 19,053 hectares of lands currently available for agriculture, while there are 56,969 hectares of lands required for agriculture, implying a deficit of 37,916 ha of land. Analysis on land capability shows that lands with eutropepts and tropudults soil with total extent of 16,650,9 hectares are potential to be developed for dryland agriculture, such as seasonal crops, while tropohemist soil is suitable for farmland development, such as lowland rice. The spatial plans in Santan 1 and Santan 2 watersheds do not have adequate lands with agricultural capability since the cultivation areas are situated in VI and VII class with limiting factor of slope and erosion. We find there is undeveloped land in the form of bushes with an extent of 12,989,3 hectares in Santan 1 watershed and 7,055.54 hectares in Santan 2 watershed as potential lands to be developed for dryland agriculture. The results of this study suggest that when establishing neighborhood and hamlet should refer to soil characteristics with certain land capability and cultivation activities not to be done on lands with slopes of >15%.